Mid‐upper arm circumference as a screening tool for identifying children with obesity: a 12‐country study. Issue 6 (30th May 2016) - Chaput, J.‐P.; Katzmarzyk, P. T.; Barnes, J. D.; Fogelholm, M.; Hu, G.; Kuriyan, R.; Kurpad, A.; Lambert, E. V.; Maher, C.; Maia, J.; Matsudo, V.; Olds, T.; et al.
Summary: Background: No studies have examined if mid‐upper arm circumference (MUAC) can be an alternative screening tool for obesity in an international sample of children differing widely in levels of human development. Objective: Our aim is to determine whether MUAC could be used to identify obesity in children from 12 countries in five major geographic regions of the world. Methods: This observational, multinational cross‐sectional study included 7337 children aged 9–11 years. Anthropometric measurements were objectively assessed, and obesity was defined according to the World Health Organization reference data. Results: In the total sample, MUAC was strongly correlated with adiposity indicators in both boys and girls ( r > 0.86, p < 0.001). The accuracy level of MUAC for identifying obesity was high in both sexes and across study sites (overall area under the curve of 0.97, sensitivity of 95% and specificity of 90%). The MUAC cut‐off value to identify obesity was 25 cm for both boys and girls. In country‐specific analyses, the cut‐off value to identify obesity ranged from 23.2 cm (boys in South Africa) to 26.2 cm (girls in the UK). Conclusions: Results from this 12‐country study suggest that MUAC is a simple and accurate measurement that may be used to identify obesity in children aged 9–11 years. MUAC may be a promising screening tool for obesity in resource‐limited settings.